answersLogoWhite

0


Best Answer

To solve for p, set up the equation

5p + 9 = p - 3

5p = p - 12

4p = -12

p = -3

to prove the answer, substitute -3 for p and prove

5(-3) + 9 = (-3) -3

-15 + 9 = -6

-6 = -6

User Avatar

Wiki User

โˆ™ 2010-02-22 18:32:49
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.8
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
2036 Reviews

Add your answer:

Earn +20 pts
Q: If P multiplied by 5 plus 9 equals p minus 3 what is the value of p?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked